Pendidikan Kewarganegaraan Sebagai Sarana Memperkuat Identitas Bangsa Indonesia - Wendy Anugrah Octavian (Departement of Mathematics Education, 2023)
This article aims to examine and provide a theoretical basis regarding Citizenship Education as a means of strengthening national identity. Indonesia is a country that has diversity and wealth which makes it the hallmark or identity of the Indonesian nation. However, at present this identity is being eroded by the influx of various external influences due to globalization. This can be a threat to the existence of the identity of the Indonesian nation. This article will discuss two main problem formulations, the urgency of strengthening the nation's national identity and how the role of Citizenship Education Courses is in strengthening national identity. The approach used in this research is qualitative by using the literature study method. Sources of data in this study used various literature, namely books and journal articles. The results of this study indicate that Citizenship Education has a very important role as a means of strengthening national identity. Either directly or indirectly, the Citizenship Education Course contains material on national identity. So that teachers can make learning more meaningful by combining various learning models and various media to maximize the role of Civics Courses in strengthening the identity of the nation.